MOLECULAR CLONING AND SEQUENCE ANALYSIS OF TES-120 GENE OF Toxocara canis EXCRETORY-SECRETORY ANTIGEN - K.T. Kavitha; C. Sreekumar; Bhaskaran Ravi Latha; A. Mangala Gowri (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The gene encoding the excretory-secretory antigen of TES-120 from larvae of Toxocara canis was cloned and the sequence was analyzed for utilization as a diagnostic molecule. The total RNA was isolated from T. canis infective larvae and reverse transcription was done with oligo dT primers to obtain complementary DNA (cDNA). Amplification by PCR was performed with cDNA as a template and specific primers of the gene of TES-120, yielding an amplicon size of 530 bp. The amplicon was cloned into pRSETa expression vector. The recombinant clones were transformed into BL21 (DE3) pLysS E. coli expression host and the clone was confirmed by colony PCR, restriction enzyme analysis and sequencing. The nucleotide sequencing of TES-120 gene of TN isolate showed 99.8 % homology with the previously published sequences of UK (U39815.1) and Venezuela isolate (KU951901.1) and 97.0 % homology with the published sequences of Iraq isolate (LC328969.1). Phylogenetic tree revealed close relationship of TN isolate with Venezuela isolate, which had a common ancestor with the UK isolate and it is distantly related to Malaysia isolate of T. cati (KP71707).